النخبة السياسية الإسلامية في تركيا و دورها في عملية التحول الديمقراطي - إيمان, دني (Sciences de l'Homme et de la Société, 2017)
الملخص: يمكن اعتبار تجربة الإسلاميين في تركيا فريدة ونوعية من عدة نواحي أهمها إيمانها منذ وقت مبكر بأهمية المدخل السياسي في عملية التغيير والإصلاح، فهي قد مارست السياسة في البرلمان والحكومة وفق نظام ديمقراطي، وآمنت بشروطه كلها، وعملت في الهامش الضيق المسموح لها به ، وبالرغم من ذلك فانتظام هذا التيار ضمن شروط اللعبة الديمقراطية، أتاح له التعبير عن طروحاته علنا وبطريقة سلمية، وهكذا تكون الديمقراطية التي كانت وسيلة لاستيعاب التيار الإسلامي والتقليل من" أخطاره" و"أصوليته" هي نفسها تحمل هذا التيار ممثلا بحزب "الرفاه " في التجربة السابقة وحزب "العدالة والتنمي " ة في التجربة السياسية الحالية إلى السلطة في تركيا الجمهورية العلمانية. Abstract: The experience of the Turkish Islamists is unique in its kind, in its strategy and its merits, including the early conviction displayed for full adherence to the political process to lead to rupture, change and reforms. This movement with an Islamic tendency has exercised politics in parliament and in government as stipulated by the conditions imposed by democracy, exploiting with all its forces, the margin of maneuver allowed, despite the constraints, the adhesion of this movement to democracy. is established without transgressions to the rules governing the democratic game, which allowed him to express the designs of his ideology openly and peacefully. Thus the same democracy which wanted to contain this movement and reduce its danger, which hoisted it to the